The effect of integration electronic mind maps into Arabic language vocabulary’s lecture on achievements of fifth-grade students in Jordan - Alomari, Akram M.; Alhorani, Mohamad E. (International Journal of Scientific Research and Management (IJSRM), 2019)
The study was conducted to investigate the integration of electronic mind map within the Arabic vocabulary instruction for fifth-grade students at Jordan. The sample included two classes chosen by the available method from the fifth grade classes in two schools in northern Jordan. One of the classes (29 pupils) whom represented the experimental group; its members studied using the strategy of Electronic Mind map. The other class (30 pupils) represented the control group. The researchers used an achievement test, as well as a collective interview conducted with the experimental group after the post-test. The results revealed that the computerized mind map reinforced students' educational accomplishment in Arabic vocabulary, increased their concentration and created the instructive process more interactive fascinating and gratifying and continue to learn. The study suggested the acceleration of the integration of mind maps in the Arabic language in several education stages. The necessity to produce schools with internet and pcs particularly within the second stage and also to require advantage of specialists within the field of educational technology to attain the highest-quality lecturers.